Based on amorphous carbon C@ZnxCd1-xS/Co3O4 composite for efficient photocatalytic hydrogen evolution. (18th March 2020) - Li, Hongying; Wang, Guorong; Zhang, Xiaojie; Jin, Zhiliang
Abstract: In this work, C@Znx Cd1-x S/Co3 O4 catalyst which with high hydrogen production activity was prepared and the catalyst was characterized by SEM, TEM, XRD, XPS, Uv–vis DRS characterization. After two-step modification, the light absorption intensity of C@Znx Cd1-x S and C@Znx Cd1-x S/Co3 O4 showed an increasing trend compared with pure Znx Cd1-x S, such phenomenon was beneficial to the visible light absorption and utilization of photocatalyst. In addition, Mott-Schottky proved that Znx Cd1-x S catalyst formed p-n heterojunction with Co3 O4 nanoparticles, which further demonstrated that the modification of Znx Cd1-x S by Co3 O4 was successful. And the hydrogen production of C@Znx Cd1-x S/Co3 O4 (30%) (1405.1 μmol) was 6.9 times that of pure Znx Cd1-x S. The improvement of photocatalytic performance can be attributed to that carbon particles accelerate the storage and transfer of electrons, and the formation of p-n heterojunction between Co3 O4 and Znx Cd1-x S promotes the separation of photogenerated carriers effectively. In this study, the introduction of amorphous carbon and Co3 O4 promoted the transfer and separation of electrons and holes greatly, thereby inhibited the recombination of carriers and provided the favorable conditions for the preparation of highly efficient and stable photocatalysts. Highlights: Novel C@Znx Cd1-x S/Co3 O4 composite is prepared. The effective separation and transport of photogenerated charge is obtained. p-n heterostructure effectively promotes carrier separation.